Trote ecológico no campus sede da Universidade Federal do Pará, Belém-PA, Brasil: memória e percepção de um legado - FERREIRA, Maria da Conceição Gonçalves (Universidade Federal do Pará, 2020)
The Federal University of Pará, created in 1957, located in the Amazon region, bordered and cut by rivers, was installed in 450 hectares of várzea area. Its implantation occurred at the cost of severe loss of the vegetal cover of great part of the designated area, resulting in great transformations in the ecosystem of the region. This study investigates the impacts caused by the Ecological Trot project implemented at the UFPA campus in Belém from 1990 to 1997. The main objective of this project was to contribute to the development of a preservation awareness and belonging to the institution's students. as well as throughout the academic community, with the pedagogical commitment to reforest and recover the soils of UFPA campus areas suffering from vegetation suppression. The project also added the idea of making the students' admission to the university more humane and less aggressive, against the abusive academic trots commonly applied in the country. The research is based on the documented or perceived memory of the project's creators and implementers and the servers that experienced the daily routine of the transformations that occurred from the application of the trot. The subjects of the research were interviewed in two distinct stages: in the first stage were interviewed, through a semistructured form, the implementers of the Ecological Trot that were part of the organizational team; in the second stage were interviewed, through a mixed form, servers that experienced the Ecological Trot. The third step was aerial satellite images of the study area to verify the tree evolution in the landscape, after applying the Ecological Trot. The results of the study showed that the Ecological Trot fulfilled its objective, demonstrated by the increase of densified areas, mainly in the forests and the banks of the Tucunduba Igarapé, which limits the Basic Professional Sector, even with the occurrence of important occasional losses of afforestation of the UFPA expansion need. It was also evidenced that the Ecological Trot became a guiding framework for subsequent actions related to the environment, spreading beyond the walls of the institution and the country. Today, in addition to preserving the tree legacy of the Ecological Trot, the Institution continues to work with other socio-environmental actions and citizen awareness among the academic community, but not forgetting the planting and replanting of new species, providing the academic community with a vast array of objects for research in all areas of knowledge and giving future generations a continuous reflection, in the sense of writing a story more harmonious with nature and the chain of life.